Interaksi Sosial Siswa di SMAN 1 Lubuk Basung - Aprilia, Silvina; Yarni, Linda (Lembaga Yasin AlSys, 2023)
Student ethics in speaking kindly to peers and to elders such as lack of respect for each other, lack of courtesy when speaking. The aim of the study was to find out the ethics of social interaction for class XI IPA students at SMAN 1 Lubuk Basung. This type of qualitative research is descriptive in nature, key informants are homeroom teachers for class XI IPA and supporting informants for class XI IPA students. Data was collected using observation data collection techniques and interviews. The results of the research were processed using descriptive analytic data analysis. The results showed that the ethics of social interaction for class XI IPA students at SMA N 1 Lubuk Basung, namely, manners in interacting include, the topics discussed should revolve around things that are useful and good, avoid talking about bad, and not useful, not lie in what he says, don't talk about other people's shortcomings, spread bad rumors, don't criticize or ridicule other people, don't act arrogant or arrogant when speaking, don't monopolize the conversation in a forum, don't raise your voice in conversations with other people, so can cause noise, criticizing people must be wise, good language and not dropping the charisma of the person being criticized, speaking must be appropriate to the conditions and situation, speaking calmly so that others can easily understand it, and speaking must be brief and clear, so as not to bore for listeners.